Specific Peak Discharge of Two Catchments Covered by Teak Forest with Different Area Percentages - Basuki, Tyas Mutiara; Adi, Rahardyan Nugroho; Wijaya, Wahyu Wisnu (Universitas Muhammadiyah Surakarta, 2017)
In watershed area, forest has important roles in relation with peak discharge. This Â research was conducted to study the impacts of teak forest on peak discharge. On-screen digitizing of IKONOS imagery was done to classify the land cover of the study area. Kejalen and Gagakan catchments covered by old teak forests by 74% and 53% respectively, were chosen as the study area. These catchments are located in Blora Regency. Automatic streamflow recorder was set at the outlet of each catchment and subsequently, peak discharges were examined from the recorded data. During the observation, there were 36 evidences of specific peak discharge. The results showed that a trend of lower peak discharges occurred in Kejalen catchment which has the higher percentage of teak forest area Â in compared to Gagakan catchment with lower percentage of teak forest area, except when extreme rainfalls happened. At rainfall of 163 mm/day, specific peak discharge in Kejalen was higher than in Gagakan catchment. Although there is a relationship between specific peak discharge and the percentage of forest cover area, the increase of specific peak discharge is not only affected by forest cover, but also affected by daily rainfall, antecedent soil moisture, and rainfall intensity. Coefficients of determination between specific peak discharge and daily rainfall are 0.64 and 0.61 for Kejalen and Gagakan catchments, respectively.